2006
DOI: 10.1016/j.bbmt.2006.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Hodgkin Disease Patients Following High-Dose Busulfan, Etoposide, Cyclophosphamide, and Autologous Stem Cell Transplantation

Abstract: Busulfan (Bu)-based preparative regimens have not been extensively investigated in Hodgkin disease (HD). The purposes of this study were to investigate the toxicity and efficacy of a novel preparative regimen of Bu 14 mg/kg, etoposide 50-60 mg/kg, and cyclophosphamide 120 mg/kg in patients with primary refractory and relapsed HD. One hundred twenty-seven patients with a median age of 33 years (range, 14-67 years) underwent transplantation. The regimen was well tolerated, with 5.5% treatment-related mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 55 publications
4
15
0
Order By: Relevance
“…dosing, similar to the conclusions of a randomized study of PK-directed IV4 versus IV16 conditioning regimens (n 5 30/group) [19]. Our reported 5-year OS in the cohort of patients receiving oral busulfan is consistent with a previous report in HL patients with a median age of 33 [20], and is corroborated by a recent study using the United States Surveillance, Epidemiology, and End Results data for patients with diffuse large B-cell lymphoma [21]. A phase II clinical trial currently being pursued is assessing the toxicity and efficacy of PK-directed once-daily i.v.…”
Section: Discussionsupporting
confidence: 93%
“…dosing, similar to the conclusions of a randomized study of PK-directed IV4 versus IV16 conditioning regimens (n 5 30/group) [19]. Our reported 5-year OS in the cohort of patients receiving oral busulfan is consistent with a previous report in HL patients with a median age of 33 [20], and is corroborated by a recent study using the United States Surveillance, Epidemiology, and End Results data for patients with diffuse large B-cell lymphoma [21]. A phase II clinical trial currently being pursued is assessing the toxicity and efficacy of PK-directed once-daily i.v.…”
Section: Discussionsupporting
confidence: 93%
“…All patients who were alive and disease free at 5 years were still in remission at 10 years post-transplant. 7,[14][15] This was similar in our study, none of the patients relapsed after 5 years.…”
Section: Discussionsupporting
confidence: 88%
“…15,[17][18][19] In our study, remission status at transplantation was found to be statistically significant for OS (p= 0.031). Different studies had different results about remission status and that could be grounded on applying different chemotherapy regimens before transplantation.…”
Section: Discussionmentioning
confidence: 45%
“…This agent has been used as an alternative to classic conditioning regimens based on carmustine to improve the tolerance/effectiveness relationship [45][46][47][48] for patients with NHL [49][50][51] or multiple myeloma (Table 3a and Table 3b). [52][53][54] In adults, thiotepa is preferentially indicated for the treatment of lymphoid malignancies with central nervous system (CNS) localization.…”
mentioning
confidence: 99%